MADRASAH DAN MASALAH IATI DIRT PENDIDIKAN ISLAM - Suprayogo, Imam (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
According to 'Undang-Undang Sisdiknas' no. 2Q of the year 2003, both the position and the status of Madrasah are on a par with the public school. Most people, however, still regard Madrasah as